2006
DOI: 10.1097/01.mao.0000176177.17636.53
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Hearing Loss in Perforations of the Tympanic Membrane

Abstract: Background-Although tympanic membrane perforations are common, there have been few systematic studies of the structural features determining the magnitude of the resulting conductive hearing loss. Our recent experimental and modeling studies predicted that the conductive hearing loss will increase with increasing perforation size, be independent of perforation location (contrary to popular otologic belief), and increase with decreasing size of the middle-ear and mastoid air space (an idea new to otology).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
194
7
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(237 citation statements)
references
References 7 publications
28
194
7
8
Order By: Relevance
“…A study conducted by Shiromany et al had patients in age range from 12 to 64 years and mean age was 26.7 ± 10.18 years (5). The mean age of patients in the present study was comparable with the other studies (6)(7)(8).Maximum patients i.e. 40% (24/60) were in age range of 18-20 years.…”
Section: Discussionsupporting
confidence: 80%
“…A study conducted by Shiromany et al had patients in age range from 12 to 64 years and mean age was 26.7 ± 10.18 years (5). The mean age of patients in the present study was comparable with the other studies (6)(7)(8).Maximum patients i.e. 40% (24/60) were in age range of 18-20 years.…”
Section: Discussionsupporting
confidence: 80%
“…The hearing loss also varies according to the size and site of the perforation. The posterior quadrant perforation has slightly more hearing loss than the anterior ones [1].…”
Section: Discussionmentioning
confidence: 85%
“…Besides ossicular integrity, there are other determinants of hearing loss in dry perforated ears, such as middle ear volume and area of perforation. Mehta et al (10) showed that hearing loss increases with increasing perforation size but that the location of the perforation had no effect. They also mentioned that hearing threshold had an inverse relation with middle ear volume.…”
Section: Discussionmentioning
confidence: 99%